KNOWLEDGE, ATTITUDE AND MYTHS ON INFERTILITY: A REVIEW ARTICLE. - Uzma Eram (International Journal of Research Science and Management, 2017)
Infertility is a disease of the reproductive system which affects both men and women with almost equal frequency. While there is no universal definition of infertility, a couple is generally considered clinically infertile when pregnancy has not occurred after at least twelve months of regular unprotected sexual activity.Psychologically, the infertile woman exhibits significantly higher psychopathology in the form of tension, hostility, anxiety,depression,self-blame and suicidal ideation.Social stigma regarding infertility is especially common across South Asia. The aim of this study was to review the literature on knowledge,attitude and myths on infertility.